2007
DOI: 10.1097/01.idc.0000239720.32336.99
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia Management in Patients With Human Immunodeficiency Virus

Abstract: Both effective antiretroviral therapy and human immunodeficiency virus (HIV) infection have been associated with changes in serum lipids. Data on the relevance of this dyslipidemia on cardiovascular risk are growing. Although guidelines for managing dyslipidemia in HIV-infected patients are available, consideration of the changing literature is important to develop a stepwise approach for management. In this review, the 2003 guidelines of Infectious Diseases Society of America and HIV Medicine Association on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
0
2
0
1
Order By: Relevance
“…A própria infecção pelo HIV é associada a um perfil lipídico pró-aterogênico caracterizado pelo aumento de triglicérides e da concentração de partículas menos densas da fração LDL do colesterol e pela redução dos níveis de HDL-c 23,24 .…”
Section: Lipodistrofia Presente (N = 16) Lipodistrofia Ausente (N = 14)unclassified
“…A própria infecção pelo HIV é associada a um perfil lipídico pró-aterogênico caracterizado pelo aumento de triglicérides e da concentração de partículas menos densas da fração LDL do colesterol e pela redução dos níveis de HDL-c 23,24 .…”
Section: Lipodistrofia Presente (N = 16) Lipodistrofia Ausente (N = 14)unclassified
“…23 A recent cohort study found that, after adjusted multifactorial analysis, there was a relationship between the use of protease inhibitors, the development of lipodystrophy and acute myocardial infarction in adults. 26 Human immunodeficiency virus infections can result in chronic oxidative stress with apoptosis of T-lymphocytes and increases in viral replication rates due to activation of nuclear factor kappa B.…”
Section: Discussionmentioning
confidence: 99%
“…The HIV infection itself is associated with a proatherogenic lipid profile characterized by increased triglycerides and a concentration of the lower density particles of the LDL fraction of cholesterol and a reduction in HDL C levels. 23,24 When compared with indinavir, nelfinavir and atazanavir, ritonavir is the protease inhibitor most associated with lipid profile abnormalities. 25 With relation to non-nucleoside reverse transcriptase, studies suggest that using nevirapine leads to fewer lipid profile abnormalities than efavirenz.…”
Section: Discussionmentioning
confidence: 99%